Female Journalists: Dwindling Interest Among College Students - Prima Virginia; Adwin Agung Kurniawan; Nessa Aulia (Universitas Multimedia Nusantara, 2026)
Research aims to identify the factors influencing the low number of female students from the first batch of the Communication Studies programme at Pamulang University choosing journalism as their major, despite female students dominating in numbers at over 50%. Employing mixed methods—quantitative and qualitative—and supported by a constructivist paradigm and standpoint theory, this research analyses the data holistically. The quantitative analysis sampled 49 female students, whilst the qualitative samples consisted of five female students. The results of the primary questionnaire data analysis revealed that respondents did not choose their major based on interest in specific subjects or lecturers, but rather had targeted specific professions aligned with their chosen major; consequently, journalism and journalists had very few applicants, or less than 20%. The results of the qualitative analysis reveal the female students’ standpoint on the journalists profession, reconstructing the experiences and perspective of journalists as a male-dominated, discrimination-prone, and intimidating workplace for women. Respondents were also reluctant to pursue journalism related to political issues, considered to be a male domain.